2022
DOI: 10.1038/s41467-022-32592-7
|View full text |Cite
|
Sign up to set email alerts
|

Earlier Alzheimer’s disease onset is associated with tau pathology in brain hub regions and facilitated tau spreading

Abstract: In Alzheimer’s disease (AD), younger symptom onset is associated with accelerated disease progression and tau spreading, yet the mechanisms underlying faster disease manifestation are unknown. To address this, we combined resting-state fMRI and longitudinal tau-PET in two independent samples of controls and biomarker-confirmed AD patients (ADNI/BioFINDER, n = 240/57). Consistent across both samples, we found that younger symptomatic AD patients showed stronger tau-PET in globally connected fronto-parietal hubs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 85 publications
3
34
0
Order By: Relevance
“…Our previous study performed individually specified PLFCS to quantitatively characterize the decrease degree and the PLFCS of the left middle temporal gyrus that yielded a powerful diagnostic efficacy of 80% for categorizing SCD from NC. Moreover, significant gray matter volume reductions, altered FC pattern and density, together with severely decreased amplitude of low-frequency fluctuation in the left MTG have been reported in previous studies on MCI [ 40 , 41 , 42 , 43 ]. These findings indicated that the MTG was a crucial network node with rich connections, and it could be a promising target in studies of the AD continuum.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Our previous study performed individually specified PLFCS to quantitatively characterize the decrease degree and the PLFCS of the left middle temporal gyrus that yielded a powerful diagnostic efficacy of 80% for categorizing SCD from NC. Moreover, significant gray matter volume reductions, altered FC pattern and density, together with severely decreased amplitude of low-frequency fluctuation in the left MTG have been reported in previous studies on MCI [ 40 , 41 , 42 , 43 ]. These findings indicated that the MTG was a crucial network node with rich connections, and it could be a promising target in studies of the AD continuum.…”
Section: Discussionmentioning
confidence: 54%
“…These findings indicated that the MTG was a crucial network node with rich connections, and it could be a promising target in studies of the AD continuum. In addition to MTG, other regional connectome alterations such as hippocampal connectivity [ 17 ] and frontoparietal control network hubs [ 43 ] were also reported on MCI and AD, and some were proven to be related to tau pathology in disease progression [ 44 ]. Therefore, other FC assessments would be used to estimate the functional abnormality and its relationship with tau burden, and additional regional connectome influenced by cognition impairment-related pathological alterations would be analyzed in further studies, which might offer new insights into the pathological interpretation of the relationship between tau accumulation and the functional connectivity and find more potential biomarkers in the AD continuum.…”
Section: Discussionmentioning
confidence: 99%
“…Fabrication of the platform was based on sphere lithography [ 26 ]. A periodic gold nano pyramid structure, with a diameter of 200 nm, was fabricated by a wafer-scale, bottom-up templating technology [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…CSF provides a means to assess neurodegenerative processes in the brain through the identification of disease-associated molecules. These molecules most often are proteins or protein fragments, including the amyloid β-protein (Aβ) and tau [ 20 , 22 , 23 , 24 , 25 , 26 , 27 ], which are amenable to analysis using a variety of techniques, including surface-enhanced Raman spectroscopy (SERS) [ 28 , 29 ]. The raw spectral information collected from CSF covers a huge multi-dimensional dataset.…”
Section: Introductionmentioning
confidence: 99%
“…Neurofibrillary tangles (NFTs) are another kind of aggregated protein seen in the brains of AD patients [ 20 ]. These NFTs consist of neuronal hyper-phosphorylated filaments of the microtubule-associated protein tau MAPT [ 21 ].…”
Section: Alzheimer´s Disease Pathology Hallmarksmentioning
confidence: 99%